Conception of Motion as Newton Law Implementation among Students of Physics Education - Eko Sujarwanto; Ino Angga Putra (Jurnal Pendidikan Sains, 2018)
Abstract: The study was conducted by giving an identification test on Newton’s laws of motion application in the form of multiple choice questions to students who were enrolled in Mechanics and Basic Physics Courses. The analysis was based on student answers and the level of student confidence in the correctness of the answers in quantitative descriptive and qualitative. The results of the analysis of identification tests were reinforced by thinking map of Newton’s laws of student presentation and followed up by interviews. The results show that students’ conceptions of motion and Newton’s laws is insufficient. Prospective teacher students are required to learn the concepts of Motion and Newton’s Law applied and influenced by common sense.Key Words: conception, Newton’s laws, motionAbstrak: Penelitian dilakukan dengan memberikan tes identifikasi aplikasi hukum-hukum Newton tentang gerak kepada mahasiswa berupa soal pilihan ganda pada mahasiswa yang terdaftar pada matakuliah Mekanika dan Fisika Dasar. Analisis didasarkan pada jawaban mahasiswa dan tingkat kepercayaan mahasiswa terhadap kebenaran jawabannya secara kuantitatif deskriptif dan kualitatif. Hasil analisis tes identifikasi diperkuat dengan thinking map hukum-hukum Newton sajian mahasiswa dan ditindaklanjuti dengan wawancara. Hasil penelitian menunjukkan konsepsi mahasiswa tentang gerak dan hukum-hukum Newton dalam kategori “Kurang Paham”. Mahasiswa calon guru perlu belajar dan mempelajari konsep Gerak dan Hukum Newton secara aplikatif dan dipengaruhi oleh common sense.Kata kunci: konsepsi, hukum-hukum Newton, keadaan gerak